Pós-colheita da cebola em função da adubação com micronutrientes - Vieira, Régis Cavalcante (2021)
The onion (Allium cepa L.) has great socioeconomic importance worldwide, as it is the third most cultivated vegetable. However, as it is highly perishable and in demand above supply, many post-harvest losses occur, caused mainly by inadequate storage conditions that considerably affect the quality of the bulbs. This study aimed to evaluate the postharvest quality of onion as a function of fertilization with micronutrients, using the cultivar “Rio das antas”. The experiment was divided into two stages: field and laboratory. In the field, an experiment was installed between June and December 2019 at Experimental Farm Rafael Fernandes, in completely randomized blocks with nine treatments and four replications. The treatments consisted of the combined doses of B, Cu and Zn. In the laboratory, the experimental design was in completely randomized blocks in 9 x 4 subdivided plots, with four replications. The treatments (micronutrients B, Cu and Zn) were arranged in the plots and the storage times were arranged in the subplots (0; 20; 40 and 60 days after harvest). Weight loss, bulb firmness, soluble solids (ºBrix), total soluble sugars, total titratable acidity, SS / TTA ratio, pH, pungency and color were evaluated. The data were subjected to statistical analysis as a function of storage time, using the Sisvar program, applying regression analysis. The combined application of doses of 1-4-1 kg.ha-1 of Boron, Copper and Zinc, respectively, presented the best results for pH, firmness and sugars during storage